Glitch-Induced Pulse Profile Change of Psr J0742-2822 Observed from the Iar - Espinoza-Romo, C (EDP Sciences, 2025)
Context. The radio pulsar PSR J0742-2822 is known to exhibit rapid changes between different pulse profile states that correlate with changes in its spin-down rate. However, the connection between these variations and the glitch activity of the pulsar remains unclear. Aims. We aim to study the evolution of the pulse profile and spin-down rate of PSR J0742-2822 in the period MJD 58810a-60149 (November 2019 to July 2023), which includes the glitch on MJD 59839 (September 2022). In particular, we looked for pulse profile or spin-down changes associated with the 2022 glitch. Methods. We observed PSR J0742-2822 with a high cadence from the Argentine Institute of Radioastronomy (IAR) between November 2019 and July 2023. We used standard timing tools to characterise the times of arrival of the pulses and to study the pulsar rotation and, particularly, the oscillations of ν. We also studied the evolution of the pulse profile. For both of them, we compared their behaviour before and after the 2022 glitch. Results. With respect to ν, we find that oscillations diminished in amplitude after the glitch. We find four different components contributing to the pre-glitch ν oscillations, and only one component after the glitch. With regard to the emission, we find the pulse profile has two main peaks. We detect an increase in the W50 of the total pulse profile of ∼12% after the glitch and we find the amplitude of the trailing peak increased with respect to the amplitude of the leading one after the glitch. Conclusions. We find significant changes in the pulse profile and the spin-down rate of PSR J0742-2822 after its 2022 glitch. These results suggest that there is a strong coupling between the internal superfluid of the neutron star and its magnetosphere, and that pulse profile changes may be led by this coupling instead of being led purely by magnetospheric effects. © The Authors 2025.